2002
DOI: 10.1109/ted.2002.804706
|View full text |Cite
|
Sign up to set email alerts
|

A power-optimal repeater insertion methodology for global interconnects in nanometer designs

Abstract: This paper addresses the problem of power dissipation during the buffer insertion phase of interconnect performance optimization. It is shown that the interconnect delay is actually very shallow with respect to both the repeater size and separation close to the minimum point. A methodology is developed to calculate the repeater size and interconnect length which minimizes the total interconnect power dissipation for any given delay penalty. This methodology is used to calculate the power-optimal buffering sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(181 citation statements)
references
References 17 publications
4
177
0
Order By: Relevance
“…The related structure is named as "Unequal buffer partitioning network" against "Equal buffer partitioning network" that was mentioned above. The optimum delay is a function of various parameters such as the buffers sizes, the interconnect segments lengths, the load and so on [9], [11], [12], [15]- [17], [19]- [22]. It is shown that for the optimization of a buffer inserted interconnect behavior, the energy-delay product minimization is better than the delay minimization.…”
Section: Repeater Insertion As a Technique For The Delay Reductionmentioning
confidence: 99%
“…The related structure is named as "Unequal buffer partitioning network" against "Equal buffer partitioning network" that was mentioned above. The optimum delay is a function of various parameters such as the buffers sizes, the interconnect segments lengths, the load and so on [9], [11], [12], [15]- [17], [19]- [22]. It is shown that for the optimization of a buffer inserted interconnect behavior, the energy-delay product minimization is better than the delay minimization.…”
Section: Repeater Insertion As a Technique For The Delay Reductionmentioning
confidence: 99%
“…By tuning wire's characteristics, it is possible to design wires with varying latency, bandwidth, and energy properties [3]. Using links that are comprised of wires with different physical properties, a heterogeneous on-chip interconnection network is obtained [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several circuit models have been proposed to compute the delay or power dissipation of repeaters such as the switch-level RC model [9], the generalized model considering slew rate [14], and the moment matching model [3]. Various design objectives are used such as delay minimization [4,12,19], power minimization [6,10,13,16,18], and cross-coupling noise reduction [1,7].…”
Section: Previous Researchmentioning
confidence: 99%